Penguatan Soft Skill Guru PAI di SDI Tebuireng ir.Soedigno Kesamben - Jazilah, Khoirul (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2019)
Abstract: This study aims to describe the competence of the Islamis Studies (PAI) teacher at SDI Tebuireng, Kesamben. The results obtained from this research  are; 1. PAI Teachers’ soft skills in SDI Tebuireng Ir. Soedigno Kesamben is very good, that consist of communication skills, time management skill, flexibility in carrying out work and responsibilities, emotion management skill, giving motivation skills, team-working skills, having ethics and morals, polite in appearance, having SQ spiritual skills, self-developing and tolerating. 2. Making efforts to strengthen PAI teachers’ soft skills at SDI Tebuireng Ir. Soedigno Kesamben that are teacher planning system, (which includes religious exams, personality psychology exams, professional examinations and practice exams), teacher-apprenticeship programs, the Quran science skill upgrading, teacher’s character upgrading, the ‘wise week’ program, students’ home visit, conducting Friday pahing prayer, rolling leadership and coffee break. It it is suggested for teachers to always develope their soft skills by reading a lot of literature and also reminding one another